PENGARUH PROFITABILITAS DAN GOOD CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK - Eling Ri Kurniati; Eky Apriani (Medikonis, 2021)
ABSTRACT The aim of this study was to examine the effect of profitability and good corporate governance toward tax avoidance. Good corporate governance was proxied by institutional ownership, an independent board of commissioners, an audit committee, and audit quality toward tax avoidance. The population in this study were mining companies listed on the Indonesia Stock Exchange in the 2014-2018 period with amount 47 companies. Samples were selected using the purposive sampling method. The total sample used in this study are 9 mining companies with a study period of 5 years, so that the samples obtained were 45 samples. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that profitability have a significant effect toward tax avoidance, while the institutional ownership, independent board of commissioners, audit committee, and audit quality are unable to establish the influence toward tax avoidance.